The Effect of Music On The Emotional Intelligence Development Of Early Childhood - Evie Destiana (International Consortium of Education and Culture Research Studies, 2017)
Childhood is the most amazing moment, all the fundamentals of growth developed during this time. Music for children can act as a vehicle that can complement each other's thoughts and feelings. The child's ability in advanced thoughts through tone, emotion (feeling) and motion can be developed through music. According to John M. Ortiz, music can be a healthy and safe stimulant. In addition, music and other sounds that can help reduce anxiety and stress. Learning music is a positive activity for children, because this activity is able to hone the physical ability, mental as well as the emotional sensitivity of a child in a balanced and important parents in developing the basic skills of music in children.